Home Program Lansia Cepokuning Cegah Demensia dan Resiko Jatuh - Priharwanti, Ardiana; Isrofah; Dwitasari, Irine; Maulana, Jaya (Yayasan Kawanad, 2023)
Elderly people are the final stage of human life, characterized by deterioration of health balance and physiological conditions that increase the risk of organ disorders. Reduced brain function can lead to various neurological and psychological disorders, delirium, and dementia. Psychomotor function, including the ability to move, act, and coordinate, may also decline with age, which may reduce agility in older adults. Older adults also experience a decline in their ability to carry out daily life and become more vulnerable to various challenges. With the growing number of elderly people in Indonesia, this issue has a significant impact on government and society. Physical and mental decline in older adults, including reduced cognitive function, is a major concern that requires appropriate management and prevention efforts. To address these problems, the Community Service Program (PKM), specifically targeting the elderly, senior citizens and BKL Anggrek RT. 05 RW. 02 in the village of Cepokokuning, provides concrete solutions to overcome this problem through the provision of health and home education programs. This program aims to improve the optimization of cognitive functions and coordination in older adults